2016
DOI: 10.1155/2016/4160568
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Fibre Layer Thickness Measurement in Normal Paediatric Population in Sweden Using Optical Coherence Tomography

Abstract: Purpose. To evaluate the correlation between peripapillary retinal nerve fibre layer (RNFL) thickness and both age and refraction error in healthy children using optical coherence tomography (OCT). Patients and Methods. 80 healthy children with a mean age of 9.1 years (range 3.8 to 16.7 years) undergoing routine ocular examination at the orthoptic section of the Ophthalmology Department were recruited for this cross-sectional study. After applying cycloplegia, the peripapillary RNFL thickness was measured in b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…However, most studies reported no significant association between age and RNFL thickness in the pediatric population [ 17 , 22 , 23 , 24 , 25 , 26 , 28 , 30 , 32 , 33 , 34 , 35 , 38 , 39 , 40 , 41 , 44 , 49 , 50 , 51 , 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, most studies reported no significant association between age and RNFL thickness in the pediatric population [ 17 , 22 , 23 , 24 , 25 , 26 , 28 , 30 , 32 , 33 , 34 , 35 , 38 , 39 , 40 , 41 , 44 , 49 , 50 , 51 , 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are studies that suggest differences between races. Caucasian, Black (Afro Americans), and Asian populations have been mostly studied until now [ 48 , 52 , 60 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…The mean total RNFLT was 104.08 ± 7.90 μm which was comparable to data obtained from previous studies. [ 10 11 12 18 25 26 27 28 29 ]…”
Section: Discussionmentioning
confidence: 99%